Optical coherence tomography assessment of the acute effects of stent implantation on the vessel wall: a systematic quantitative approach. Issue 23 (10th August 2009) - Gonzalo, N; Serruys, P W; Okamura, T; Shen, Z J; Onuma, Y; Garcia-Garcia, H M; Sarno, G; Schultz, C; van Geuns, R J; Ligthart, J; Regar, E
Abstract : Objective: To observe and characterise vessel injury after stenting using optical coherence tomography (OCT), to propose a systematic OCT classification for periprocedural vessel trauma, to evaluate its frequency in stable versus unstable patients and to assess its clinical impact during the hospitalisation period. Setting: Stenting causes vessel injury. Design and interventions: All consecutive patients in whom OCT was performed after stent implantation were included in the study. Qualitative and quantitative assessment of tissue prolapse, intra-stent dissection and edge dissection were performed. Results: Seventy-three patients (80 vessels) were analysed. Tissue prolapse within the stented segment was visible in 78/80 vessels (97.5%). Median number of tissue prolapse sites was 8 (IQR 4–19), mean (SD) area 1.04 (0.9) mm 2 . Intra-stent dissection flaps were visible in 69/80 vessels (86.3%) (median number 3 (IQR 1.25–6), maximum flap length 450 (220) μm). Fifty-five out of 80 vessels (68.8%) showed dissection cavities (median number 2 (IQR 0–4.75), maximum depth 340 (170) μm). Edge dissection was visible in 20 vessels (mean (SD) length flap 744 (439) μm). The frequency of tissue prolapse or intra-stent dissection was similar in stable and unstable patients (95.6% vs 100%, p = 0.5 for tissue prolapse; 91.1% vs 82.9%, p = 0.3 for intra-stent dissection). There were no events during the hospitalisation period. Conclusions: OCT allows a detailed visualisation of vessel injury after stent implantation and enables a systematic classification and quantification in vivo. In this study, frequency of tissue prolapse or intra-stent dissections after stenting was high, irrespective of the clinical presentation of the patients, and was not associated with clinical events during hospitalisation.